Prevention of Bone Loss in a Model of Postmenopausal Osteoporosis through Adrenomedullin Inhibition - Martínez-Herrero, Sonia; Larrayoz, Ignacio M.; Ochoa-Callejero, Laura; Fernández, Luis J.; Allueva, Alexis; Ochoa, Ignacio; Martínez, Alfredo (Frontiers in Physiology, 2016)
Despite recent advances in the understanding and treatment options for osteoporosis, this condition remains a serious public health issue. Adrenomedullin (AM) is a regulatory peptide with reported activity on bone remodelling. To better understand this relationship we built an inducible knockout for AM. An outstanding feature of knockout mice is their heavier weight due, in part, to the presence of denser bones. The femur of knockout animals was denser, had more trabeculae, and a thicker growth plate than wild type littermates. The endocrine influence of AM on bone seems to be elicited through an indirect mechanism involving, at least, the regulation of insulin, glucose, ghrelin, and calcitonin gene-related peptide (CGRP). To confirm the data we performed a pharmacological approach using the AM inhibitor 16311 in a mouse model of osteoporosis. Ovariectomized females showed significant bone mass loss, whereas ovariectomized females treated with 16311 had similar bone density to sham operated females. In conclusion, we propose the use of AM inhibitors for the treatment of osteoporosis and other conditions leading to the loss of bone mass.